اللغة العربية في مراسلات الإدارة الجزائرية دراسةتقييمية تقويميةإدارة بلدية الوادي أنموذجا - مصمودي, دليلة; بن عمر, الشيماء (University of Eloued جامعة الوادي, 2024)
جاء بحثنا مجيبًا عن إشكالية مفادها : ما واقع اللغة العربية في مراسلات إدارة بلدية ، أجابت عنها خطّة كان قوامها مدخل نظري و فصل أول تحليلي تقييمي تقويمي للمراسلات ، تلاها فصل ثانٍ قائم على دراسة ميدانية سابرة لآراء ثلاثون (30) محرر للمراسلات على مستوى البلدية العينة ، حيث نسج المنهج الوصفي الإحصائي التحليلي معالم هذا البحث ، لنتوصل في الأخير إلى نتيجة فيصلية ألا و هي أنّ اللغة العربية تعتبر في المقام الأول في تحرير المراسلات الإدارية في بلدية الوادي وهذا لا ينفي وقوع موظفيها في عديد الصعوبات للعمل بقواعدها و ضوابطها . Our study aimed to explore the inherent characteristics of the Arabic language within the context of municipal administration correspondence. To achieve this goal, we adopted a comprehensive approach that incorporated a solid theoretical framework as well as an initial analysis, evaluation, and critical examination of the correspondence. Which followed by the second chapter, we conducted a field investigation wherein we interviewed thirty (30) correspondence editors working at the municipal level to gain further insights. By employing a systematic blend of descriptive, statistical, and analytical methodologies, we successfully identified the distinctive aspects of our study. Ultimately, a definitive resolution has been reached, highlighting the prioritization of the Arabic language when editing administrative correspondence within El Oued Municipality. Nevertheless, it is important to acknowledge the numerous obstacles encountered by employees as they strive to comply with the intricacies and regulations of this language. Notre recherche a été menée pour répondre à la problématique suivante : quelle est la situation de la langue arabe dans la correspondance administrative d'une municipalité ? La méthodologie adoptée comprenait une introduction théorique suivie d'une première partie d'analyse et d'évaluation de la correspondance. Ensuite, une deuxième partie basée sur une étude de terrain approfondie des opinions de trente (30) rédacteurs de correspondance au niveau de l'échantillon municipal a été réalisée. La méthode descriptive, statistique et analytique a été tissée pour identifier les caractéristiques de cette recherche. En conclusion, il a été établi que la langue arabe est principalement utilisée dans la rédaction de la correspondance administrative à la municipalité d'El-Oued, bien que ses employés rencontrent plusieurs difficultés pour respecter ses règles et ses normes
لسانيات عامة